Towards an Ethical Framework for Eradicating Poverty: A Critical Reflection on Amartya Sen’s Capability Theory in the Light of Catholic Social Teaching - Irudayam, Chrles (Asian Horizons, 2009)
“Indeed, the test of orderliness in a country is not the number of millionaires it owns, but the absence of starvation among its masses” (Mahatma Gandhi). Universal Declaration on Human Rights 1948, article 25(1) says, “Everyone has the right to a standard of living adequate for the health and well-being of himself or herself and of his or her family, including food, clothing, housing and medical care and necessary social service.” But in reality, according to UNDP annual report 2006, more than 800 million people suffer from hunger and malnutrition, 1.1 billion people do not have access to clean drinking water and, every hour, 1,200 children die from preventable diseases mostly in sub-Saharan Africa and southern Asia. This phenomenon of poverty is a paradoxical one, because the universe harbours enough resources for all to have a life worthy of human being and technology has made tremendous break-through in almost all aspects of life and its findings should guarantee a dignified living to all. Yet, in spite of all this, poverty remains a very substantial feature of human existence because the poor do not have access to natural resources and the economic growth or technological innovation has not benefited the bottom two-thirds of the world population.